miR-1247 Functions by Targeting Cartilage Transcription Factor SOX9 - Martinez-Sanchez, Aida (American Society for Biochemistry and Molecular Biology, 2013)
microRNAs are a large and essential class of gene regulators that play key roles in development, homeostasis, and disease. They are necessary for normal skeletal development, and their expression is altered in arthritis. However, the specific role of individual microRNAs is only beginning to be unraveled. Using microRNA expression profiling in healthy human articular cartilage cells (chondrocytes), we identified miR-1247 expression as highly correlated with that of the differentiated cell phenotype. Transcribed from the DLK1-DIO3 locus, the function of miR-1247 is completely unknown. In mice its expression level was relatively high in cartilage tissue, and correlated with cartilage-associated microRNA miR-675 across a range of 15 different mouse tissues. To further probe miR-1247 function, overexpression and inhibition studies were performed in isolated human chondrocytes. Modulation of miR-1247 was found to exert profound phenotypic effects altering expression levels of cartilage master regulator transcription factor SOX9. SOX9 is essential for cartilage development and subsequent function throughout life, and mutations in this gene result in severe dwarfism. Putative miR-1247 binding sites were further investigated using luciferase reporter assays, which indicated binding of miR-1247 to a highly conserved region in the coding sequence of SOX9 but not in its 3′-UTR. Interestingly, depletion of SOX9 in human chondrocytes resulted in increased levels of the mature, processed microRNA, suggesting a negative feedback loop between miR-1247 and its target SOX9.